FEATURES OF HISTORICAL DEVELOPMENT OF THE LEGISLATION OF THE AZERBAIJAN REPUBLIC AND UKRAINE ON CRIMINAL LAW PROTECTION OF JUSTICE IN THE XIX - XX CENTURIES - Ахмедов, Вусал Алігісмат огли (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article investigates the historical development of the Ukrainian and Azerbaijani criminal law on the protection of justice. Methods of research: historical, comparative, research legal documents, in particular historical ones. Results: The author highlighted the peculiarities of criminal legal protection of relations in the field of justice on the Ukrainian and Azeri lands during the period of the Russian Empire, Soviet power, and examined the specifics of the norms of Muslim criminal law. Discussion: influence of historical legal acts on modern criminal laws of Ukraine and the Republic of Azerbaijan.